The Ethics of Information Systems: The Present State of the Discussion and Avenues for Future Work - Bock, Alexander C.; España, Sergio; Gulden, Jens; Jahn, Katharina; Nweke, Livinus Obiora; Richter, Andreas (29th European Conference on Information Systems 2021 (ECIS 2021), 2021)
Despite occasional pleas to incorporate the ethics of information systems into the field’s research agenda, the analysis of the moral ramifications of information systems has remained unsystematic in nature. Work on a remarkable variety of ethical issues has appeared, but the field has yet to produce a coherent conception of how it construes and studies the ethics of information systems. In this research-in-progress paper, we report on work to redress the situation by addressing three goals. First, we provide an overview of contributions made to the study of ethics in information systems research in recent decades. Second, we present a classificatory scheme to organize past and future work on the subject. Third, we identify themes that have received little attention to date, proposing routes for future work. In particular, we find that our field has yet to fully explore the moral implications of the very artifacts of its own design. We conclude with a call to action for information systems researchers to work towards a structured account of ethics as part of the field’s research agenda.